Evaluation of the effect of jasmonic acid elicitation on composition of pigments and biological activities in green callus of neem (Azadirachta indica) - Ahmad Fauzi, Nurul Syazwani; Abd Rahim, Muhamad Hafiz; Abdul Majid, Nazia; Othman, Rashidi; Yaacob, Jamilah Syafawati (Frontiers in Sustainable Food Systems, 2022)
This study was carried out with the aim of determining the effects of jasmonic acid (JA) elicitation on the bioactive pigments’ biosynthesis and the antioxidant activities in green callus of Azadirachta indica of two different ages (4- and 8-week-old). Plant tissue culture technique was employed to induce the formation of green callus from leaf explants of A. indica on Murashige and Skoog (MS) medium supplemented with 0.6 mg/L thidiazuron (CM) and three different concentrations of JA (2, 4 and 6 mg/L). The methanolic extracts from the green callus were used for determination of total chlorophyll content (TCh), total carotenoid content (TC), total anthocyanin content (TAC), total phenolic content (TPC), and total flavonoid content (TFC) through colorimetric and HPLC analyses. The highest amount of yield was obtained from CM and 2 mg/L JA (2JA) extracts for 4- and 8-week-old samples, respectively. Phytochemical screening revealed the presence of alkaloids, flavonoids, phenols, tannins, and terpenoids in all 4- and 8-week-old samples elicited with 2, 4 and 6 mg/L JA.. The highest value for TAC, TCh, TC, TPC, and TFC of 4- and 8-week-old samples were from callus cultured on media supplemented with 6 mg/L JA (6JA) and 4 mg/L JA (4JA), respectively. The lowest IC50 values were found to be 8.29 ± 0.10 mg/mL (6JA) for 4-week-old and 7.73 ± 0.03 mg/mL (4JA) for 8-week-old samples. The highest Ferric Reducing Antioxidant Power (FRAP) values obtained in this study were 90.60 ± 1.55 g/g (6JA), and 74.59 ± 3.91 g/g (4JA), respectively for 4- and 8-week-old samples. Moreover, Pearson’s correlation analysis revealed a significant correlation between TAC, TCh, TC, TPC, and TFC with ABTS and FRAP assays. Overall, these findings suggested that JA supplementation into the culture media significantly increase the chlorophyll, carotenoid, anthocyanin, phenolic and flavonoid contents and JA concentrations at 6 mg/L JA and 4 mg/L JA yielded the highest pigments content in 4-weeks-old and 8-weeks-old callus, respectively.